A Comprehensive Review of Recent Advancement in Optical Communication Networks - Vinita (International Journal of Computer Sciences and Engineering, 2025)
Optical fiber communication along with the advanced optical networking technologies and advanced modulation formats is an evolving field of research. The enormous bandwidth and long distance reach of optical networks makes them a suitable candidate to be used in backhaul networks. This paper presents a comprehensive review of various advanced optical networks: Wavelength Division Multiplexing (WDM) based networks, Radio over Fiber (RoF) networks, Passive Optical Networks (PONs) and recently proposed Elastic Optical Networks (EONs) along with recent work reported in literature. A briefs description of optical amplifiers and several architectural advancements in these optical networks is also discussed in a holistic manner .